STUDI EKSPERIMEN KARAKTERISTIK DINAMIK BETON DENGANAGREGAT KASAR BATU APUNG - Petrus Berno Lando; Harry Janto Jepira; Firnimus Konstantinus Bhara (Program Studi Teknik Sipil, 2023)
This experimental study of the dynamic characteristics of concrete with coarse aggregate of pumice is an attempt to determine the dynamic characteristics of lightweight concrete with coarse aggregate of pumice compared to conventional concrete using vibration analysis under conditions of several ages of concrete. The dynamic characteristics themselves include mass (m), damping (c), and stiffness (c) experimentally. Vibration tests are carried out by providing an impulse load in the form of a punch or impact force, the vibration response of the test object is measured using the Myfrequency application installed on an Android cellphone. In the end, on the twenty-eighth day the experimental results showed the average values as follows: for the weight of pumice stone 17,536 kg and conventional concrete 26,857 kg, for the mass of pumice stone 1.7 kgs2/m and conventional concrete 2.7 kgs2/m, for attenuation of pumice stone 6.67% and conventional concrete 6.1%, for the natural frequency value of pumice 16.56 Hz and conventional concrete 11.39 Hz and for the stiffness of pumice 512.6 N/mm and conventional concrete 369.7 N/mm.